2000
DOI: 10.1007/978-1-4612-1170-9
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Processes and Orthogonal Polynomials

Abstract: Library of Congress Cataloging-in-Publication Data Schoutens, Wim. Stochastic processes and orthogonal polynomials / Wim Schoutens. p. cm.-(Lecture notes in statistics; 146) Includes bibliographical references and index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
288
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 315 publications
(297 citation statements)
references
References 0 publications
4
288
0
5
Order By: Relevance
“…More recent work has shown that an important class of orthogonal polynomials belongs to the Askey scheme of the hypergeometric polynomials [17]. In this section, we briefly review the theory of hypergeometric orthogonal polynomials; we adopt the notation of [21,22].…”
Section: The Askey Scheme Of Hypergeometric Orthogonal Polynomialsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent work has shown that an important class of orthogonal polynomials belongs to the Askey scheme of the hypergeometric polynomials [17]. In this section, we briefly review the theory of hypergeometric orthogonal polynomials; we adopt the notation of [21,22].…”
Section: The Askey Scheme Of Hypergeometric Orthogonal Polynomialsmentioning
confidence: 99%
“…The Askey scheme, which is represented as a tree structure in figure 1 (following [22]), classifies the hypergeometric orthogonal polynomials and indicates the limit relations between them. The 'tree' starts with the Wilson polynomials and the Racah polynomials on the top.…”
Section: The Askey Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Since corr(ξ k−1 , ξ k ) = t k−1 /t k = 0, ±1, the assumption [33, (10)] holds true, too. Finally, notice that Weso lowski's α k = 1, and his (27) we see that D = 0 if and only if C = b. Thus [33, (11)] hold true.…”
Section: Conditional Variancesmentioning
confidence: 85%
“…We can solve this equation for E(X 3 u |F ≤s ), as (27) implies that C = b. Using (24) and (19), the answer simplifies to…”
Section: Hence (29) Exmentioning
confidence: 99%